2015
DOI: 10.1037/a0037070
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating multiple marginalizations: Experiences of South Asian LGBQ individuals.

Abstract: Drawing from minority stress (Meyer, 2003) and feminist multicultural (Brown, 1994) theories, the present study investigated the additive and interactive relations between 2 types of external minority stress (heterosexist discrimination and racist events) and 4 internal stress processes related to identifying as a South Asian American lesbian, gay, bisexual, and queer (LGBQ) person (internalized heterosexism, acculturation, enculturation, and outness as LGBQ) with psychological distress. With 142 participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…In Method 5.A, the analysis of intersectionality frames categories as having multiple main effects, which reflects the assessment of additive effects, typically within an analysis of variance or multiple regression framework. Not to be confused with additive approaches (i.e., approaches that are not intersectional; see Else-Quest & Hyde, 2016), additive effects have been reported in studies invoking intersectionality (e.g., Sandil, Robinson, Brewster, Wong, & Geiger, 2015; Szymanski & Gupta, 2009; Szymanski & Henrichs-Beck, 2014). Crenshaw (1991) described additive or multiple main effects when she argued that sometimes Black women experience double discrimination, that is, discrimination on the basis of both race and gender.…”
Section: Component 5: Data Analytic Strategiesmentioning
confidence: 99%
“…In Method 5.A, the analysis of intersectionality frames categories as having multiple main effects, which reflects the assessment of additive effects, typically within an analysis of variance or multiple regression framework. Not to be confused with additive approaches (i.e., approaches that are not intersectional; see Else-Quest & Hyde, 2016), additive effects have been reported in studies invoking intersectionality (e.g., Sandil, Robinson, Brewster, Wong, & Geiger, 2015; Szymanski & Gupta, 2009; Szymanski & Henrichs-Beck, 2014). Crenshaw (1991) described additive or multiple main effects when she argued that sometimes Black women experience double discrimination, that is, discrimination on the basis of both race and gender.…”
Section: Component 5: Data Analytic Strategiesmentioning
confidence: 99%
“…A number of these studies have been carried out with specific population groups, such as those living with HIV/AIDS (e.g., [ 34 37 ]) or low-income populations (e.g., [ 38 , 39 ]). Mental health outcomes are the most commonly examined (e.g., [ 28 , 29 , 32 34 , 37 46 , 48 52 ]), although physical health/self-rated health (e.g., [ 29 , 36 , 44 , 46 ]), health behaviours (e.g., [ 35 , 40 , 45 , 53 ]), wellbeing (e.g., [ 32 , 40 , 47 ]) and healthcare outcomes [ 7 ] have also been assessed. Direct comparisons are difficult due to the variability of the measurement of discrimination across the studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of acculturated AAPIW, over 40% of participants reported currently experiencing moderate to severe depression while 57% of these AAPIW did not have depression (Augsberger, Yeung, Dougher, & Hahm, 2015). Studies have shown that stress related to assimilating into American culture, experiences of racial and gender discrimination, and history of sexual abuse exacerbated the mental and psychological distress of AAPIW (Hong, Walton, Tamaki, & Sabin, 2014;Hahm, Kolaczyk, Lee, Jang, & Ng, 2012;Sandil, Robinson, Brewster, Wong, & Geiger, 2015). Yet many AAPIW with mental illnesses choose not to access mental health care services primarily due to the stigma surrounding mental illness and decreased perceived need for specialty services (Appel, Huang, Ai, & Lin, 2011;Augsberger et al, 2015;Kimerling & Baumrind, 2005).…”
mentioning
confidence: 99%